Does a vegetarian diet have an impact on oral health? A literature review - Stawińska-Dudek, Julia; Józefowicz, Wiktoria; Brzoza, Martyna; Machaj, Damian; Stawińska, Kornelia (Journal of Education, Health and Sport, 2025)
Introduction and Purpose: Vegetarianism is a diet with high intake of plants and exclusion of meat and poultry. Vegetarian diets are divided into vegan (no animal products), lactovegetarian (no animal meat, but includes milk and eggs), pescovegetarian (eating fish) and semivegetarian (occasional meat consumption) The effect of plant-based diet on oral health is still uncertain and research results are mixed. This review summarizes effects of vegetarian diet on periodontal health, dental erosion, oral microbiome and caries prevalence. The state of knowledge: According to the studies, periodontal health is improved in vegetarians, who show better periodontal indicators than omnivores. Vegetarians have a higher frequency of developing NCCL. Tooth erosion is more common in vegetarians because of their high intake of acidic foods, which can cause enamel abrasion and sensitivity. However, some results suggest that there is no significant relationship between diet and erosion. Results on the effects of a vegetarian diet on the oral microbiome and the incidence of caries are mixed. Some studies show no diet-related differences, while others note favorable microbial profiles in vegetarians and a higher prevalence of Candida species compared to omnivores. Some studies show slightly lower DMFT scores in vegetarians, but these differences are often not statistically significant. Conclusions: The relationship between a vegetarian diet and oral health is complex and modified by many confounding variables, such as gender, age, dietary composition, lifestyle or oral hygiene habits. Due to the ambiguous results, more research needs to be conducted on the effects of a vegetarian diet on oral health, especially as it relates to the oral microbiome and the prevalence of caries.